The impact of the transition to CAPI and a new fieldwork provider on the HILDA Survey - Watson, N (My University, 2010)
The HILDA Survey underwent two major changes in wave 9. The first was the change to a new fieldwork provider and the second was a change of mode from pen and paper interviewing (PAPI) to computer-assisted personal interviewing (CAPI). While the change of mode was largely inevitable over the course of the project, the change of fieldwork provider provided the impetus for the change of mode at the same time. This paper describes the key differences in operations and provides an assessment of the impact on the data quality.
Paper Series No. 2/10, December 2010
Keywords: Surveys and Survey Methodology -- Fieldwork; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Fieldwork; Surveys and Survey Methodology